Effect of proanthocyanidin on ultrastructure and mineralization of dentine collagen. (December 2017) - Epasinghe, D.J.; Burrow, M.F.; Yiu, C.K.Y.
Highlights: Proanthocyanidin, a naturally available collagen cross-linker from grape seed, alters the ultrastructure of demineralized dentine collagen matrix. The structural changes caused by proanthocyanidin harden the collagen matrix and enhance its modulus of elasticity. The proanthocyanidin-biomodified collagen matrix promotes dentine remineralization. Abstract: Objective: Proanthocyanidin (PA) is a natural collagen cross-linker that has been used in dentine matrix biomodification for reparative and preventive therapies. This study evaluated the ultrastructure of collagen after its interaction with PA. Furthermore, the mineralization of PA-biomodified collagen matrix was observed. Methods: Ten freshly extracted sound human molars were sectioned into 0.5 mm × 1.7 mm × 7 mm beams for ultrastructural evaluation of PA and dentine matrix under Field Emission Scanning Electron Microscopy (FESEM) and Transmission Electron Microscopy (TEM). Specimens for TEM were completely demineralized and divided into three groups according to PA treatments: deionized water, 2% PA and 6.5% PA. The specimens were fixed, dehydrated, sectioned and examined using TEM. Specimens for FESEM were lightly conditioned with EDTA and similarly divided into the three groups for observation using FESEM. Type I collagen from calf skin was used to analyse the mineral interaction after treatment with 6.5% PA. Formvar- and carbon-coated 400-mesh Ni grids (EMS, Hatfiels, PA, USA) were placed over a 2 mg/mL collagen solution prepared from calf skin-derived Type I collagen to achieve self-assembly of collagen fibrils. Grids were treated with 6.5% PA and divided into two groups. One group was floated over a remineralization solution containing 20 mM HEPES, 2.25 mM CaCl2 -2H2 O, 1.35 mM KH2 PO4, 3.08 mM NaN3 and 130 mM KCl and the other group was over a CPP-ACP solution (Tooth mousse 1:100 dilution with deionized water). The floating samples were kept in a 37 °C and 100% humidity chamber. Grids were taken out at selected time durations (24 h, 48 h and 72 h for mineralization solution/24 h for CPP-ACP) and observed under TEM without staining. Selected area electron diffractions (SAEDs) were performed at 110 kV. Results: Following treatment of demineralized dentine collagen matrix with PA, the size and number of interfibrillar spaces were reduced. The collagen fibrils aggregated together with a reduction in porosity. A characteristic banding pattern of collagen fibrils was observed under TEM. Treatment of PA-biomodified collagen fibrils with remineralization solution increased mineral aggregation along its long axis, when compared to the control group. Furthermore, treatment of PA-biomodified collagen fibrils with CPP-ACP solution enhanced mineral uptake and deposition as well as initiated apatite formation within 24 h. Conclusion: Proanthocyanidin alters the ultrastructure of demineralized dentine collagen matrix. The PA-biomodified collagen matrix promotes remineralization.